Faktor-Faktor Penentu Kebugaran Jasmani Pekerja (Tinjauan Literatur 2015–2025) - Artamalia Rizky Fareza; Mochammad Bagus Qomaruddin; Muji Sulistyowati (Poltekkes Kemenkes Padang, 2026)
The main issue addressed in this study is the low level of physical activity and the increasing sedentary lifestyle among workers, which negatively impacts physical fitness and work productivity . This study aims to analyze the relationship between a healthy lifestyle and workers’ physical fitness based on recent scientific evidence. The method used is a literature review with a narrative-descriptive approach conducted through three stages: identification, screening, and article selection. Literature was searched in Scopus, PubMed, and Google Scholar databases, yielding 114 articles, which were reduced to 31 after screening, and finally 10 articles met the inclusion criteria and were analyzed using content analysis. The results show that workers with higher physical activity levels had lower absenteeism (36.3 days/year) compared to less active workers (64.4 days/year), along with increased productivity (r=0.46; p=0.005). Approximately 73.2% of workers adopted personal fitness programs after intervention, and digital-based interventions significantly reduced work-related stress. In conclusion, integrating healthy lifestyle practices with organizational support and digital technology is an effective strategy to improve physical fitness, mental health, and worker productivity sustainably.